Evaluation of heritage character in the European zone of Kota Lama Surabaya post-revitalization through an urban design elements approach - Flandi Tito Pratama (Journal of Placemaking and Streetscape Design, 2026)
Background: The revitalization of the European Zone represents an effort by the Surabaya city government to improve the quality of the area without erasing its historical value and identity. Previous studies have generally assessed the success of revitalization based on either the physical condition of buildings or the activities within the area, treated separately, while the relationship between urban design elements and heritage character remains rarely discussed. This study aims to analyze the heritage character of the European Zone in Kota Lama Surabaya post-revitalization through eight urban design elements: land use, building form and massing, circulation and parking, open space, pedestrian ways, activity support, signage, and preservation. Methods: This study employs a descriptive qualitative method using field observation, documentation, and literature review. Findings: The results are then synthesized with four heritage character variables: physical urban form, spatial legibility, visual character, and heritage value. The findings indicate that the heritage character of the European Zone is formed through the interrelation of mutually reinforcing urban design elements that collectively shape the area's overall heritage character. Although the revitalization has successfully improved the physical quality of the area, the scope of intervention remains limited to a few main corridors, resulting in an uneven formation of the area's character. Conclusion: This study demonstrates that heritage character is determined not only by the presence of historic buildings but also by the relationships among elements that shape spatial structure, visual identity, area legibility, and historical value. These findings are expected to serve as a reference for the evaluation and future planning of heritage area revitalization. Novelty/Originality of this article: This study introduces an integrated framework linking urban design elements and heritage character to evaluate heritage-sensitive revitalization and cultural placemaking in public spaces.